Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.2172/1677466
|View full text |Cite
|
Sign up to set email alerts
|

Offshore Wind Resource Assessment for the California Pacific Outer Continental Shelf (2020)

Abstract: Department of Energy (DOE) reports produced after 1991 and a growing number of pre-1991 documents are available free via www.OSTI.gov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 21 publications
(30 reference statements)
1
53
0
1
Order By: Relevance
“…The main data source is the network of buoy-based wind speed measurements from the National Data Buoy Center, maintained by the National Oceanic and Atmospheric Administration (National Data Buoy Center, 1971). These data have been used to characterize the wind resource in offshore California (Wang et al, 2019;Optis et al, 2020c), the US offshore Atlantic (Optis et al, 2020b), and the Great Lakes (Doubrawa et al, 2015). These buoys generally provide years worth of wind speed measurements at heights of less than 5 m and are of high quality.…”
Section: Introductionmentioning
confidence: 99%
“…The main data source is the network of buoy-based wind speed measurements from the National Data Buoy Center, maintained by the National Oceanic and Atmospheric Administration (National Data Buoy Center, 1971). These data have been used to characterize the wind resource in offshore California (Wang et al, 2019;Optis et al, 2020c), the US offshore Atlantic (Optis et al, 2020b), and the Great Lakes (Doubrawa et al, 2015). These buoys generally provide years worth of wind speed measurements at heights of less than 5 m and are of high quality.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to popular belief, wind speeds are not always higher at 500 m compared to 100 m (Bechtle et al 2019), which was confirmed by workshop participants (Weber et al 2021), as well as an analysis conducted at NREL with WRF simulations over Hawaii, the Pacific Northwest, and the mid-Atlantic Coast (the methodology used for California in Optis et al [2020] was replicated for Hawaii and the Pacific Northwest). Figure 12 (left panels) shows the 20-year average maximum wind speed in the layer between 100 m and 500 m, and (right) the 20-year average difference between 100-m and 500-m wind speeds.…”
Section: Wind Shear and Airborne Wind Energy Resource In The United Statesmentioning
confidence: 92%
“…We consider a 20-year numerical data set recently developed by the National Renewable Energy Laboratory to provide accurate cost estimates for floating wind in the California OCS (Figure 1). As described in detail in Optis et al (2020), this product includes a single WRF setup that is run for a 20-year period (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019), and an additional 15 WRF ensemble members 100 run over a single year (2017), which were selected because of strong data coverage from the network of buoy and coastal radar observations used for model validation. All of the simulations are run with the common attributes in Table 1 -Reanalysis forcing product: selected between ERA5, developed by the European Centre for Medium-Range Weather Forecasts (Hersbach et al (2020)), and the Modern-Era Retrospective analysis for Research and Applications, Version 2 ( Gelaro et al (2017)), developed by the National Aeronautics and Space Administration.…”
Section: Numerical Simulation Setupmentioning
confidence: 99%